KORELASI REGISTRASI TENAGA KESEHATAN TERHADAP KOMPENTENSI TENAGA KESEHATAN DALAM PELAYANAN KESEHATAN MASYARAKAT - Sri Retno Widyorini (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
Health as one of the elements of general welfare must be realized through various health efforts in the context of comprehensive and integrated health development supported by a national health system. Health workers who will carry out health services to the community must have a STR (Surat Tanda Registrasi/Registration Certificate) issued by the government as the person in charge of public health services. Physicians as one of the health workers are responsible for providing health services in accordance with applicable legislation namely Law Medical Practice and Doctor's Code of Ethics. Doctors who practice health services to the community at the hospital are bound by the Doctor's Code of Ethics and are also bound by the Hospital By Laws as an internal provision of the hospital.